First report of some resupinate Polyporales from Pithoragarh region of Uttarakhand (India) - Sanyal, Sanjeev Kumar; -, Ritu; Dhingra, Gurpaul Singh (Mushroom Research, 2015)
Eight species of resupinate, non-poroid Polyporales (Hyphoderma puberum, H. setigerum, Phanerochaete galactites, P. sordida, P. tuberculata, Phlebia centrifuga, P. radiata and Phlebiopsis gigantea) are being described first time from Pithoragarh region of Uttarakhand (UK). All the species are based on collections made during 2011 from different localities in Uttarakhand, India.